Elizabeth Arden's Strategy in Winning the Millennial Market Competition through Celebrities - Rukmini Triastuti; Palupi Lindiasari Samputra; Achmad Sanusi (Budapest International Research and Critics University, 2022)
These digital influencers are third parties who have high popularity and do not always come from artists or public figures but have accounts with many followers. Instagram is a social media platform that is used by beauty teachers, or later also known as beauty vloggers because they often create and post videos about beauty. The phenomenon of digital influencers is growing along with the development of the digital world. The results of the research in the form of the role of digital influencers are associated with the context of promoting a product. Celebrities who have served as ambassadors for Elizabeth Arden are Vendela Kirsebom to promote products, while in the digital era, the role of social media is very important, especially influencers. The purpose of this study is to examine digital marketing strategies using influencers through social media. The methodology used is qualitative. The results of the study compete in a healthy manner to reach a large market in Indonesia, by utilizing technology through influencers in the beauty sector. To find out Elizabeth Arden's company marketing strategy through social media with influencers.